PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Vicky Aulia Rismita Sari; Sri Sudarsi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to test and analyze the effect of Profitability (ROA), Leverage (DAR), and Liquidity (CR) on company value (Tobin’s Q). The sampling method used in this study is puposive sampling, so that as many as 199 sample data were obtained form manufacturing companies in the consumption subsector listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. The analysis technique uses multiple linear regrassion. The test results show that profitability and leverage have a positve and significant effect on the value of the company, while liquidity has a negative and significant effect on the value of the company. Keywords: Company Value, Profitability, Leverage, and Liquidity